PELANGGARAN MAKSIM KESANTUNAN BERBAHASA DI LINGKUNGAN SMP NEGERI 10 KENDARI - Sahur Saerudin (Seshiski: Southeast Journal of Language and Literary Studies, 2025)
Language not only functions as a means of conveying information, but also reflects social attitudes, cultural values, and norms of politeness in human interactions. In the context of education, especially in elementary schools, polite language is an important aspect because it plays a role in shaping the character and social skills of students. This study aims to describe the forms of violations of linguistic politeness maxims and the factors behind them in verbal interactions at SMP Negeri 10 Kendari. This study uses a qualitative approach with a descriptive method. The research data consists of verbal statements obtained from interactions between teachers and students, students and students, and students and other school officials. Data analysis was conducted using a pragmatic approach based on Leech's politeness principle theory, specifically the maxims of wisdom, praise, and sympathy. The results show that violations of politeness in language still frequently occur in everyday communication in the school environment. Violations of the maxim of wisdom are evident in students' speech when they complain or make demands to teachers and canteen staff in an impolite manner. Violations of the maxim of praise are evident in the use of harsh, demeaning, and insulting words among students, such as ridicule and sarcasm, which can threaten the self-esteem of the addressee. Meanwhile, violations of the maxim of sympathy are seen in students' lack of empathy towards friends who are experiencing difficulties, which are instead responded to with ridicule. These violations have the potential to trigger conflict and damage social harmony in schools. Therefore, this study recommends the need to continuously instill the value of polite language through teacher role modeling and habituation in the learning process in order to create a polite, harmonious, and character-building school environment